Non-invasive measurement method of skin conditions by using Dermalab® combo - Ab. Hadi, Hazrina; Awadh, Ammar Ihsan JawaD; Mohd Hanif, Nadzira; Md Sidik, Nur Fatin Akmal; Mohd Rani, Mohd Rajaei Nuruddin; Mohd Suhaimi, Muhamad Syafiq (2014)
Introduction: Skin as a protective barrier from exogenous substances. The aim of the study was to evaluate the realibility of the DermaLab Combo in measuring transepidermal water loss (TEWL) and skin hydration.